DISEMINASI TEKNOLOGI PROBIO_FM UNTUK PENGOLAHAN PAKAN ITIK KEPADA PETANI PENGGARAP LAHAN PASCA TAMBANG TIMAH - Rufti Puji Astuti; Evahelda Evahelda; Indra Ferianto; Ipan Guspian (Yayasan Education and Social Center, 2023)
The integrated crop-livestock-fish farming systems between rice and duck is the potential to optimize the use of post-tin mining to develop agricultural activities in Bangka Belitung Islands Province. The success of the Mekar farmer group in rice farming in the area of post-tin mining is yet followed by optimizing the use of rice bran waste as the source of feed ingredient. Currently, the farmers face difficulty in mastering the agricultural technology, as a result, the rice bran waste as the duck feed is applied without any feed processing. The objective of the community service is to empower society in utilizing the Probio_FM technology to make duck feed with rice bran waste as the essential ingredient. The methods of community service were implemented in three stages: socialization, demonstration & training, as well as monitoring & evaluation. The qualitative descriptive analysis was conducted to analyze the data. The community service discovered that the farmers had utilized the Probio_FM technology in feed processing by producing the fermented bran feed for the duck. The effect of technology utilization was that the bran for animal feed was more likable, able to reduce the bad odor of animal environment, as well as the effective and efficient feed management systems. Furthermore, the knowledge on agricultural technology and behavior of livestock farmers had positively improved in utilizing the rice bran waste as the source of feed ingredient. The use of Probio_FM should be sustainable and was the potential to be optimized in integrated farm management in post-tin mining land. It could be a solution to reduce the dependency on antibiotics used to support disease control. It could also provide the solution to the feed cost problem to achieve environmental-friendly livestock farming activity